MODEL KONSTRUK KECERDASAN EMOSIONAL SISWA SD - Sumarno, Sumarno (Jurnal Sekolah Dasar, 2015)
Abstract: The current study was intended to obtain the description of the construct model of emotional intelligence of the elementary school students in Medan city. This study utilized two exogenous variables which were parenting and teachersâ competence and two endogenous variables as well which were the teaching and learning quality and emotional intelligence. There were 511 students and 68 teachers coming from 11 schools schools as the samples of the study. The results suggested that the studentsâ emotional intelligence was 82% affected by the parenting and 34% was influenced by the teaching and learning. The teachersâ competence gave 12% contribution to the teaching and learning which implied that the teaching and learning quality was dominantly affected by factors other than the 4 teachersâ competences.Keywords: construct model, emotional intelligent, elementary school studentsAbstrak: Tujuan penelitian ini untuk mendapatkan gambaran model konstruk kecerdasan emosional siswa SD Kota Medan. Pada penelitian ini melibatkan dua ubahan eksogen, yaitu: pola asuh dan kompetensi guru, serta dua ubahan endogen, yaitu: kualitas pembelajaran dan kecerdasan emosional. Sampel 11 sekolah, dengan jumlah 511 siswa; dan 68 guru. Hasil penelitian menunjukkan bahwa kecerdasan emosional siswa SD 82% dipengaruhi oleh pola asuh orang tua; dan 34% oleh kualitas pembelajaran. Kompetensi yang dimiliki guru memberi sumbangan sebesar 12% terhadap kualitas pembelajaran, hal ini menunjukkan bahwa kualitas pembelajaran dominan dipengaruhi oleh faktor lain di luar 4 kompetensi guru.Kata Kunci: Model Konstruk, Kecerdasan Emosional, Siswa SD.